2017
DOI: 10.1088/1748-605x/aa6521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca/P molar ratios on regulating biological functions of hybridized carbon nanofibers containing bioactive glass nanoparticles

Abstract: Biological functions of hybridized carbon nanofibers (CNFs) depend closely on the incorporated bioactive components. For hybridized CNFs containing bioactive glass (BG) nanoparticles (CNF/BG), chemical compositions of BG nanoparticles might have decisive effects on their cell affinity and osteocompatibility. Herein, three hybridized CNF/BGs were produced by incorporating 68S-type BG nanoparticles with different Ca/P molar ratios (1.0, 1.67 or 2.5) into CNFs via a sol-gel/electrospinning and carbonization metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Many types of nanofibrous composites have been produced, with the aim of mimicking the natural extracellular bone tissue matrix [ 115 , 171 , 172 , 173 , 174 ]. In recent years, hybridized carbon nanofibers (CNFs) containing inorganic nanoparticles have been reported as materials with great potential for bone tissue repair [ 54 , 175 ]. When compared to organic–inorganic nanofibers, CNF hybrids have distinguished characteristics for bone repair, as they favor the fixation and proliferation of bone cells, such as osteoblasts and bone mesenchymal stromal cells (BMSCs).…”
Section: Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many types of nanofibrous composites have been produced, with the aim of mimicking the natural extracellular bone tissue matrix [ 115 , 171 , 172 , 173 , 174 ]. In recent years, hybridized carbon nanofibers (CNFs) containing inorganic nanoparticles have been reported as materials with great potential for bone tissue repair [ 54 , 175 ]. When compared to organic–inorganic nanofibers, CNF hybrids have distinguished characteristics for bone repair, as they favor the fixation and proliferation of bone cells, such as osteoblasts and bone mesenchymal stromal cells (BMSCs).…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Furthermore, nanofibers with different and complex morphology, such as a porous, hollow, or core-shell structure, can be produced with these methods [ 39 , 51 ], expanding the use of these ceramic nanofibers in biomedical applications. Among the materials produced by these techniques, titania, calcium phosphate, alumina, zirconia, calcium silicate, silica, and bioactive glasses can be cited [ 23 , 45 , 48 , 50 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramic coatings, like sphene-based (CaTiSiO 5 ) coatings, can promote early cell/implant surface interactions and osteoblast proliferation and differentiation due to Ca and Si dissolution from the sphene coating [ 17 , 18 ]. In addition, bioactive glasses are used as bioactive coatings for bone scaffolds [ 19 ] and for porous titanium implants [ 20 ]. Coatings based on the organic bone phase are also used for improving implant/bone responses [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the samples shown that the apatite layer begins to be appeared after immersion but did not covered the entire surface as shown in figures 8, 9 and 10. The Ca/P ratio values of All samples before and after immersion were also different as shown below in the table 2 below; The glass has higher Ca/P ratio has higher tendancy to form Ca layer which is useful in biomedical applications than lower Ca/P ratio after immersion [14].…”
Section: After Immersionmentioning
confidence: 99%